(untitled) (Journal of Nepal Geological Society, 1982)
The Quaternary fluvio-lacustrme sediments of Kathmandu Valley arc characterized by the occurrence of low quality lignite. The lignites are more confined to the lower part of this deposition in the Lukundol Formation, consisting of clay, silt, sand and coarse sand. These lignites show ambivalent characters between lignite and peat.